Scalable framework for green large cognitive radio networks. Issue 3 (20th September 2019) - Daha Belghiti, Imane; Berrada, Ismail; El Kamili, Mohamed
Abstract : Cognitive radio networks (CRNs) have the capacity to be aware of the conditions of their operating environment, and dynamically reconfigure their own characteristics in order to reach the best available performances. These performances may be seriously impacted when the number of users in CRNs grows significantly. This study deals with efficient energy consumption and interference avoidance in large CRNs. To enhance the network lifetime, a new framework combining cognitive hierarchical clustering and the coalitional game is introduced. In this study, a new CRLEACH protocol is proposed and the well‐known LEACH protocol is used in CRNs. The authors prove theoretically that their coalition model with a new strategic learning algorithm leads to Nash equilibrium. Finally, the network performances of their framework are illustrated by numerical results.